2005
DOI: 10.1002/14651858.cd002961.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Critical incident audit and feedback to improve perinatal and maternal mortality and morbidity

Abstract: Background Audit and feedback of critical incidents is an established part of obstetric practice. However, the effect on perinatal and maternal mortality is unclear. The potential harmful effects and costs are unknown. Objectives Is critical incident audit and feedback effective in reducing the perinatal mortality rate, the maternal mortality ratio, and severe neonatal and maternal morbidity? Search methods We searched the Cochrane Pregnancy and Childbirth Group’s Trials Register (30 November 2010) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 12 publications
3
69
0
Order By: Relevance
“…Improving quality of care using audit, including maternal and perinatal death audit and standards-based audit A Cochrane systematic review on audit and feedback concluded that audit can improve professional practice [58,59]. What is also clear is that audit is a method of evaluating and documenting what is so often lacking in the health system or 'enabling environment' with regard to personnel, skills, equipment or drugs to be able to provide at least the minimum acceptable level of care.…”
Section: Adaptations Of the General Cmnh-lstm Emonc Packagementioning
confidence: 99%
“…Improving quality of care using audit, including maternal and perinatal death audit and standards-based audit A Cochrane systematic review on audit and feedback concluded that audit can improve professional practice [58,59]. What is also clear is that audit is a method of evaluating and documenting what is so often lacking in the health system or 'enabling environment' with regard to personnel, skills, equipment or drugs to be able to provide at least the minimum acceptable level of care.…”
Section: Adaptations Of the General Cmnh-lstm Emonc Packagementioning
confidence: 99%
“…We conducted a random effects meta-analysis using STATA version 10.0 statistical software (STATA Corp, College Station, TX, USA) and report the Mantel-Haenszel pooled risk ratio and corresponding 95% confidence interval (CI). Assessment of the impact of perinatal mortality audit is complex because the audit cycle and implementation of recommended actions are rarely carried out as part of a randomized trial [22] and other factors may also contribute to a measured reduction in mortality. One recent systematic review of interventions to prevent stillbirths identified 1 review and 12 intervention studies on the impact of perinatal mortality audit, with the majority from high-income countries.…”
Section: Evidence For Auditmentioning
confidence: 99%
“…Methodical and detailed case review is commonly used as a strategy to improve health professionals' care of pregnant women, 190 not only through documenting the number and causes of morbidity and mortality, but also through identifying preventable factors. 3,9 Two approaches have been taken nationally to learning from adverse incidents in maternity care: external anonymised case review (confidential enquiries) 2,3 and local (facility-based) reviews using tools such as root cause analysis.…”
Section: Introductionmentioning
confidence: 99%